EFFECT OF PLANTAGO OVATA MUCILAGE USED AS NATURAL SUPERDISINTEGRANT ON RAPIMELTS TABLET OF METACLOPRAMIDE HCL - Abhinav kumar Tripathi; Hemendra Gautam (Journal of Biomedical and Pharmaceutical Research, 2019)
Formulation, development and optimization of rapimelts containing metoclopramide HCl using natural superdisintegrant To isolate mucilage from the plantago ovata husk powder by pregelatinization method. To prepare priliminary trial batches of repimelts using β cyclodextrin with different ratio of drug and polymer. To evaluate the drug polymer complex and finally which polymer and ratio of drug and polymer is better to formulate final formulation. To achieve taste masking of drug. To prepare preliminary trial batches of rapimelts using plantago ovata mucilage as natural superdisintegrant and crosspovidone as synthetic superdisintegrant by direct compression method. To evaluate the prepared rapimelts for various properties like friability, hardness, wetting time, water absorption ratio, disintegration time, drug content, drug etc. Identifying the key variables and their levels for applying factorial design and to optimize one formulation. To evaluate the final batches and find out the optimized batch based on statistical optimization using experimental design. To compare the optimized formulation with marketed preparation. To carry out stability studies of optimized batch as per ICH guidelines. The aim of the present investigation was to Formulate, designed, and evaluates plant agoovata mucilage used as a natural superdisintegrant was to developed and optimized rapimelts containing Metoclopramide HCL. Keywords: Rapimelt , Superdisintegrant, Rapimelt Super disintegrate, Metaclopramide hydrochloride